Evaluation of spatial interpolators for improving the mapping of soil chemical attributes in banana cultivation in the Tocantins State, Brazil (Research, Society and Development, 2021)
The aim of this study is to evaluate the quality of different interpolators for the spatial distribution of soil chemical attributes in banana cultivation. Soil samples were collected at 10 different points, at depths of 0.0-0.20 m and 0.20-0.40 m. For spatialization of the chemical attributes of the soil, the performance of the Ordinary Kriging (KO) and Inverse Distance Power (IPD) interpolators were evaluated through cross validation, and the KO had the spherical, exponential and Gaussian models evaluated, as well as the IPD had its performance evaluated in exponents 2, 3 and 5. It was found, through asymmetry and kurtosis, values between 0 and 3, thus indicating the normality of the data. The lowest coefficients of variation were found for the attributes pH and V% (depth of 0.00-0.20 m) and Ca2+ (depth of 0.20-0.40 m). For all other attributes, the variation coefficients found were above 20%. Higher values were presented for the attributes Mg2+, K, H + Al3+. Among the interpolators chosen with the best performance, it can be said that 20% of the results demonstrate that the IPD-2 interpolator stood out, as well as the IPD-3. The IPD-5 showed the best performance in 40% of the results. The geostatistical interpolators did not perform satisfactorily, and the interpolator KO Spherical model, at no time behaved with the best performance among all the interpolators tested. The KO model Exponential interpolator had the best performance in 15% of the results, and the KO Gaussian model excelled in only 5% of the results.